2019
DOI: 10.1088/1755-1315/315/5/052015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity evaluation of aqueous extracts of chickpea and lentil seedlings

Abstract: The aim of the study was to explore the antioxidant activity of aqueous extracts of leguminous crop seedlings - chickpea and lentils. For the study of antioxidant activity, an in vitro method of autooxidation of adrenaline in an alkaline medium was used. The process of adrenaline autooxidation was investigated as a model reaction of quinoid oxidation, proceeding through a series of intermediate stages with the formation of the final product of adrenochrome. The accumulation of the adrenaline autooxidation inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Antioxidant capacity (AC) of legumes is due to active micro and macro elements (polysaccharides, vitamins, amino acids proteins) 38 . In this study, germinated lentils (Masoor) contained maximum ACs than dried lentils (Masoor) similarly the work of Dalaram et al 39 but contrary to lentils of Gubanenko et al 40 and Zhao et al 29 . Researchers supported that AOA (Antioxidant activity) increased as the germination time increased 25 , e.g., in mung beans, soybeans, black beans 33 , lentil seeds 41 , kidney beans 14,16 , chickpea seeds, fenugreek seeds, lentil seeds 26 and lupine seeds 36 .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Antioxidant capacity (AC) of legumes is due to active micro and macro elements (polysaccharides, vitamins, amino acids proteins) 38 . In this study, germinated lentils (Masoor) contained maximum ACs than dried lentils (Masoor) similarly the work of Dalaram et al 39 but contrary to lentils of Gubanenko et al 40 and Zhao et al 29 . Researchers supported that AOA (Antioxidant activity) increased as the germination time increased 25 , e.g., in mung beans, soybeans, black beans 33 , lentil seeds 41 , kidney beans 14,16 , chickpea seeds, fenugreek seeds, lentil seeds 26 and lupine seeds 36 .…”
Section: Discussionsupporting
confidence: 67%
“….In this research work, the TPCs of germinated legumes were observed in the following order: Red beans (Phaseolus vulgaris) 15 40. > Masoor (Lensculinaris) 11.76 > Mung (Vigna radiata) 10.2 > Mash (Vigna mungo) 8.93 > Cowpea (Vigna unguiculata) 3.46 > Black chickpae (Cicer arietinum) 2.79 > White chickpeas (Cicer arietinum) 2.52 mg GAE/g.…”
mentioning
confidence: 66%
See 1 more Smart Citation